2021
DOI: 10.1007/s10943-021-01391-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Depression, Anxiety and Stress Levels with Religious Coping Strategies Among Turkish Pregnant Women During the COVID-19 Pandemic

Abstract: The aim of this study was to investigate the depression, anxiety, stress levels, and religious coping strategies of Turkish pregnant women during the COVID-19 pandemic. Of the pregnant women involved in this study (N = 327), 74.6% were concerned about their health, whereas 85.9% had concerns about the health of the fetus during the COVID-19 pandemic. It was found that 19.9% had extremely severe depression, 97.9% had extremely severe anxiety, and 52.3% had severe stress symptoms. Religious coping scores of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Of the 31.9% who reported high levels of fear of COVID-19 infection [7], in addition to fear of COVID-19 infection, social distance such as travel restrictions and economic recession were reported to be significantly associated with depressive symptoms [12]. In addition, 32.1% and 36.4% of respondents felt that they or their family members were susceptible to COVID-19, respectively [7], and 74.6% and 85.9% of pregnant women were concerned about their own health or the health of their fetus, respectively [34].…”
Section: Risk Factors Of Depression Among Pregnant Women During the C...mentioning
confidence: 99%
“…Of the 31.9% who reported high levels of fear of COVID-19 infection [7], in addition to fear of COVID-19 infection, social distance such as travel restrictions and economic recession were reported to be significantly associated with depressive symptoms [12]. In addition, 32.1% and 36.4% of respondents felt that they or their family members were susceptible to COVID-19, respectively [7], and 74.6% and 85.9% of pregnant women were concerned about their own health or the health of their fetus, respectively [34].…”
Section: Risk Factors Of Depression Among Pregnant Women During the C...mentioning
confidence: 99%
“…Although traditionally the largest scholarship on workplace mobbing studies is associated with such scientific fields as psychology, law, sociology and management, a broader interdisciplinary approach, which would be useful for a deeper understanding of the phenomenon, is still needed ( Fahie and Dunne, 2021 ). In this context, it is significant that a quarter of a century ago the World Health Organization (WHO) acknowledged the importance of an individual’s spiritual needs and religious beliefs for health and quality of life ( World Health Organization, 1998 ) and that further research has confirmed that religiosity helps to cope with stress, fear, and anxiety ( Prazeres et al, 2021 ), to overcome depression ( Bakır et al, 2021 ) and psychological trauma accompanied by post-traumatic stress disorder ( Harris et al, 2021 ). However, despite the existing evidence, religious spiritual assistance for the victims of mobbing, which responds to the person’s specific needs, remains under-researched in the scientific literature, both theoretically and empirically ( Vveinhardt and Deikus, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women faced difficulties in obtaining adequate antenatal care during the COVID-19 pandemic due to limited access to health care [ 14 , 15 ] and were reluctant to visit antenatal care due to fear of COVID-19 infection, resulting in a decrease in antenatal care visits [ 16 ]. Furthermore, pregnant women were concerned about their own and their babies’ health [ 17 ]. A study reported that pregnant couples were more likely comply with COVID-19 preventive behaviors due to a heightened fear of COVID-19 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%